Male partners’ perceptions of maternal near miss obstetric morbidity experienced by their spouses - Mbalinda, Scovia N (Reprod Health, 2015)
BACKGROUND: Severe obstetric complications have potential negative impact on the family and household of the survivors, with potential negative effects during (and in the aftermath of) the traumatic obstetric events. The objective was to gain deeper understanding of how severe obstetric complications are perceived by male partners, and their impact on the livelihoods of the family and community. METHODS: Data was collected through 25 in-depth narrative interviews with male partners of women with severe obstetric morbidity. The interviews occurred 4-12 months after the traumatic childbirth events. To gain a deeper understanding of the meanings and spouses attach to the experiences, we employed the notions of social capital and resilience. RESULTS: Male partners’ perceptions and experiences were mostly characterized by losses, dreams and dilemmas, disempowerment and alienation, seclusion and self isolation or reliance on the social networks. During the aftermath of the events, there was disruption of the livelihoods of the partners and the whole family. CONCLUSION: While a maternal near miss obstetric event might appear as a positive outcome for the survivors, partners and caregivers of women who experience severe obstetric morbidity are deeply affected by the experiences of this life-threatening episode.